Effects of Storage on Resistant Staphylococcus Aureus Strains - Ajagbe, J.M. * , Kumurya, A.S. , Rabiu, M. , Dogo, E.B., Ega, B. , Tukur, A.D. , Opalekunde, A.B. , and Yusuf, A.A. (Sokoto Journal of Medical Laboratory Science)
Storage of bacterial isolates is critical for research, diagnostic, and teaching purposes. The various methods of storage depend on intended use of the organism and time, which ranges from short-term to long-term storage. Other methods include Cryoprotectants, Freezing samples, Freeze-drying. Storage effects on bacteria may have important implications, in which Methicillin Resistant Stapylococcus aureus (MRSA) strains are not exceptional. A literature search was carried out and identified 84 papers. After exclusions, a total of 28 were found relevant. This review explored the fact that, effects of storage on MRSA strains are enormous. This include reduced susceptibility to antibiotics, loss of mecA gene, reduced or loss of viability among others. It is therefore of paramount importance that more concern should be given to the influence that storage conditions have on characteristics of the stored strains of resistant Stapylococcus species. In order to determine the effects of storage on resistant Staphylococcus aureus, various relevant literatures using internet, textbooks, journals, periodicals e. t. c. were explored and information relevant to the subject matter were obtained. Recommendations on possible ways for proper maintenance and preservation of resistant Staphylococcus aureus strains were made.